Isolated left vertebral artery terminating in the posterior inferior cerebellar artery in South African patients: Two case studies - Bukola R. Omotoso; Rohen Harrichandparsad; Indheresan G. Moodley; Kapil S. Satyapal; Lelika Lazarus (Elsevier, 2022)
Introduction: The right and left vertebral arteries supply approximately 24% of total brain blood flow volume in adult individuals. The vertebral artery is segmented into four parts, and each of the segments of the artery has associated morphologic variation. The variation in origin, level of entering the transverse foramen, tortuosity, fenestration, and hypoplasia has been reported. However, the incidence of isolated left vertebral artery terminating in the posterior inferior cerebellar artery is rare. Isolated left vertebral artery terminating in the posterior inferior cerebellar artery has been identified as a risk factor for rotational vertebral artery syndrome, lateral medullary infarction, stroke, or transient ischemia attack. Case presentation: We report on two isolated left vertebral arteries terminating in the posterior inferior cerebellar artery observed in two male patients examined by multidetector computed tomography angiography. The ipsilateral vertebral arteries are hypoplastic and enter the transverse foramen at an atypical level. Conclusion: Imaging the entire course of the vertebral artery from the origin to the point of convergence to form the basilar artery may be necessary to decide a treatment strategy for interventions in the vicinity of the vertebral artery. Details of clinical sequelae in this case report will contribute to the necessity of studying the prevalence of this variation in patients with cerebrovascular events. Knowledge of anatomical variation will help interpret preoperative images and analyze potential consequences of intentional arterial occlusion during endovascular procedures and open repair surgeries.